Pengaruh Keselamatan Kesehatan Kerja (K3) Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Matsuzawa Pelita Furniture Indonesia - Suherman, Aleida Istiqomah; Suroso, Suroso; Anggela, Flora Fatricia (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to determine partial or simultaneous relationship between occupational health safety (K3) and the work environment on the performance of PT employees. Matsuzawa Pelita Furniture Indonesia. The method used in this research is a quantitative method. The research sample consisted of 70 employees of PT Matsuzawa Pelita Furniture Indonesia. The sampling technique in research uses a saturated sampling method. The analysis model used in this research is a multiple linear regression analysis model using the F test and t test with a significance level of 5%. The research results show that there is no partial influence between occupational health safety (K3) on the performance of PT employees. Matsuzawa Pelita Furniture Indonesia with a t table value (1.680 < 1.994 or t count < t table ) and there is a partial influence of the Work Environment on employee performance at PT Matsuzawa Pelita Furniture Indonesia with a t table value (-2.327 < 1.994 or t count < t table). The magnitude of the influence between occupational health safety (K3) and the work environment on the performance of PT employees. Matsuzawa Pelita Furniture Indonesia was 10.1% while 89.9% was influenced by other variables such as work culture, work discipline, etc.